Development of a Transformational–Distributed Leadership Model to Build Teacher Collaborative Culture and Professionalism in Elementary Schools - Usman Usman; Abdul Majid; Syed Kaleem Ullah Shah Bukhari (Vidya Karya, 2026)
Low levels of teacher collaboration and varying professional competence remain key challenges in improving the quality of elementary education. This study aims to develop and examine the effectiveness of a transformational–distributed leadership model in fostering a collaborative teacher culture and enhancing professional competence. This study employed a research and development (R&D) approach based on the model of Walter R. Borg and Meredith D. Gall, consisting of planning, model development, trial, and revision stages. The participants included principals, teachers, and school supervisors. Data were collected through questionnaires, interviews, observations, and document analysis and analyzed using both quantitative and qualitative approaches. The findings indicate that the developed model is effective in improving teacher collaboration and professional competence. The mean score of teacher collaboration increased from 2.85 to 4.21, while professional competence improved from 3.02 to 4.18. The model also demonstrated high levels of practicality and relevance. Qualitative results revealed increased teacher engagement in joint planning, collaborative decision-making, and professional development activities. The novelty of this study lies in integrating transformational and distributed leadership into a validated operational model that simultaneously targets collaborative culture and teacher professional competence in elementary schools. In conclusion, the transformational–distributed leadership model is effective and offers a practical framework for school leaders to promote sustainable, collaboration-based school improvement.